Hsien Wu and his major contributions to the chemical era of immunology - Ebrahimi Mohammad (De Gruyter, 2021)
One of the first biological fields to achieve a formal chemical wing is believed to be immunology, and in the early twentieth century, many investigators have studied this field in terms of chemical reactions. Hsien Wu was one of China’s outstanding biochemist leaders during the first half of the twentieth century, an influential immunology scientist. By introducing his academic and scientific background, I elaborate on Hsien Wu’s achievements in the immunochemical period. Wu has solved one of the most serious issues on the accurate perception of immunology, and he made quick and universal attention in this regard. Hsien’s most fundamental contribution to this field is his concentration on quantitation, chemical approaches, and physicochemical, opening a new window for other scientists to find out more about the chemical approaches and theories.